Findings of OCT‐angiography compared to fluorescein and indocyanine green angiography in central serous chorioretinopathy. Issue 10 (12th June 2018) - Min, Jing‐Yu; Lv, Yanan; Yu, Suqin; Gong, Yuan‐Yuan
Abstract : Purpose: The present study analyzed the appearances of optical coherence tomography angiography (OCTA) in patients with central serous chorioretinopathy (CSC) based on fluorescein angiography (FA) and indocyanine green angiography (ICGA). Method: In the current case series, 54 eyes of 50 patients diagnosed as CSC were evaluated retrospectively. OCTA, FA, and ICGA were performed on each patient. Two trained observers examined the OCTA images independently to confirm and compare the choriocapillary appearance with that on FA/ICGA. Also, the leakage of vessels on FA, perfusion of choroidal blood flow on ICGA, blood flow density, and vascular morphology on OCTA, as well as, the effect of serous retinal detachment (SRD) on imaging were observed. Furthermore, the image findings of contralateral eyes were included. Results: 47/54 eyes (corresponding to 43 patients in 50 patients) were finally diagnosed with CSC that presented a leakage on FA and dilated vessels on ICGA, and the corresponding areas could be recognized on OCTA. However, in some of the cases (15 eyes, 31.9%), a portion of the leakage lesion on FA did not overlap completely with that on OCTA. On the OCTA B‐scan, six eyes did not show a choriocapillary flow signal under subretinal fluid (SRF) with a median SRD height of 485 µm, despite the dilated vessels on ICGA. Approximately, 21 contralateral eyes without SRD and leakage presented dilated vessels on ICGA; however, only 13 eyes could be recognized on OCTA. In addition, seven eyes presented CSC on FA/ICGA but manifested explicit abnormal vascularization beneath the retinal pigment epithelium (RPE) on OCTA. Conclusion: FA/ICGA remains the gold standard for the diagnosis of CSC and cannot be completely replaced by OCTA. However, in some cases displaying hot‐spots CNV, OCTA can contribute toward a definite diagnosis. The SRD height may exert a shielding effect on the choriocapillary flow signals on OCTA. Lasers Surg. Med. 50:987–993, 2018. © 2018 Wiley Periodicals, Inc.